“The feature, or — perhaps — the features” of handwriting development level in handwriting identification analysis - Skubisz-Ślusarczyk, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
As the handwriting process is a multistage action, we start learning it in pre-school and complete it during the graphic maturity period. We begin with expressing our thoughts and emotions by means of images, to proceed with imitating parts of the writing signs, and in the next stage — their complete patterns. While learning how to write, we try to precisely reproduce a presented model. At this stage, the graphism demonstrates no individual features. Individualised handwriting occurs only after the writing activity has become automated. It is only then that the writer does not produce the letters or letter groups in the same manner.The factors which affect letter shaping, expressed in handwriting features, have a respective impact on the value and quality of the written record. The handwriting features can be numbered among so-called communication features. Since they are defined by means of description, the vast majority of handwriting features belong to low-specificity features. This also refers to handwriting development — a feature presented without a comprehensive and unambiguous classification.
Keywords: handwriting analysis; identification analysis; handwriting features; handwriting features classification; handwriting development level